Foucault’s «disciplinary society» and Luhmann’s autopoetic developed society - Τάση Σμαρώ (The Greek Review of Social Research, 2014)
The main focus of this study is the term “disciplinary society” as found in Foucault’s work. The term is examined particularly on the basis of Foucault’s lectures in Brazil in 1973. The point of departure here is the truth-finding method (enquête) which Foucault attempts to find in Sophocles’ work “Oedipus the King”. According to Foucault this archaic method of truth-finding was the basis of the method of observation (examen) which turned out to be a fundamental method for establishing facts of a case within the realm of criminal proceedings. Presenting the developmental stages of these methods, Foucault finally reaches examination, which he regards as a milestone in disciplinary action and therefore as a basis of the disciplinary society. This attempt to explain Foucault’s disciplinary society also takes into account the approaches of Luhmann’s system theory which will eventually prove the validity of Foucault’s theory on the disciplinary society.